Muscular and extramuscular clinical features of patients with anti-PM/Scl autoantibodies. (5th June 2018) - De Lorenzo, Rebecca; Pinal-Fernandez, Iago; Huang, Wilson; Albayda, Jemima; Tiniakou, Eleni; Johnson, Cheilonda; Milisenda, Jose C.; Casal-Dominguez, Maria; Corse, Andrea M.; Danoff, Sonye K.; Christopher-Stine, Lisa; Paik, Julie J.; et al.
Abstract : Objective: To define the clinical features of myositis patients with anti-PM/Scl-75 and/or anti-PM/Scl-100 autoantibodies at disease onset and during the course of disease and compare them to patients with other forms of myositis. Methods: In this longitudinal cohort study, the prevalence and severity of clinical features at disease onset and during follow-up were compared between anti-PM/Scl-positive patients and those with the antisynthetase syndrome (AS), dermatomyositis (DM), and immune-mediated necrotizing myopathy (IMNM). Results: Forty-one anti-PM/Scl-positive, 132 AS, 178 DM, and 135 IMNM patients were included. Although muscle weakness was a presenting feature in just 37% of anti-PM/Scl-positive patients, 93% eventually developed weakness. Unlike the other groups, anti-PM-Scl-positive patients had more severe weakness in arm abductors than hip flexors. Interstitial lung disease was a presenting feature in just 10% of anti-PM/Scl-positive patients, but occurred in 61% during follow-up; fewer patients with DM (13%, p < 0.001) and IMNM (6%, p < 0.001) and more patients with AS (80%, p < 0.05) developed interstitial lung disease during the course of disease. Mechanic's hands (80%), Raynaud syndrome (78%), sclerodactyly (66%), telangiectasias (66%), esophageal reflux disease (61%), subcutaneous edema (46%), puffy hands (39%), and calcinosis (39%) occurred more frequently in anti-PM/Scl-positive patients than in the other groups. Although 30% of anti-PM/Scl-positive patients met criteria for systemic sclerosis, less than 5% had renal crisis or finger ulcerations. No differences were found between patients with only anti-PM/Scl-100 or only anti-PM/Scl-75 autoantibodies. Conclusions: Unlike patients with DM, AS, or IMNM, anti-PM/Scl-positive patients have weaker arm abductors than hip flexors. Anti-PM/Scl-positive patients also have the most extensive extramuscular features.